IMPROVING THE STUDENTS’ VOCABULARY MASTERY BY USING TREE DIAGRAM ON THE EIGHTH GRADE STUDENTS’ OF SMP DWIJENDRA IN THE ACADEMIC YEAR 2019/2020 - Delvi Amelia Susanti Lede; Ni Wayan Swarniti (Widyasrama, 2020)
The aim of this research was to know the process of improve the students vocabulary mastery throught tree diagram strategy for eighth grade students of SMP Dwijendra Denpasar in academic year 2019/2020. The subject was the students of VIII B in the academic year 2019/2020. The subjects of this research were consisted of 30 students of second grade. The instruments that was used in collecting the data was test, interview and observation.The method used in this research was Classroom Action Research (CAR). Based on the result of this research showed that there was a development on the students’ vocabulary mastery, it was be seen from the mean score of pretest were 61,5 the mean of posttest cycle 1 was 73,8 and the mean score of posttest cycle 2 was 83,5. In addition there were 3 students (10%) who passed Minimum Mastery Criterion (KKM) in the pretest. Meanwhile, in cycle 1, there were 12 students (40%) who passed Minimum Mastery Criterion (KKM) and it gained which was in the posttest cycle 2 there were 27 students (90%) who passed Minimum Mastery Criterion. So, the criteria of success were achieved. Furthermore, the result of observation and interview showed that the students were motivated in the teaching-learning process during the implementation of Tree Diagram Strategy.